Water reclamation from anodizing wastewaters by removing reactive silica with adsorption and precipitation methods. (15th January 2023) - Acosta-Herrera, Andrea Alejandra; Hernández-Montoya, Virginia; Tovar-Gómez, Rigoberto; Pérez-Cruz, María A.; Montes-Morán, Miguel A.; Rangel-Vázquez, Norma A.; Cervantes, Francisco J.
Abstract: Water stress is a current environmental menace mainly driven by over exploitation of aquifers, which is triggering poor water quality with high concentration of minerals in extracted groundwater. Particularly, silica is widespread in natural water supplies due to weathering processes of silicates occurring in contact with water, light, air, and other factors. However, due to groundwater over extraction the concentration of silica has increased during the last years in aquifer reservoirs from Aguascalientes State (México). In this context, it is very important to note that the removal of silica compounds from water is challenging and different methods can be used to avoid embedding problems in different industries. In the present work, the removal of reactive silica from synthetic solutions as well as from real wastewaters from an industrial anodizing process was studied using adsorption and chemical precipitation methods. Twelve commercial materials of different nature were used for adsorption tests, while seven precipitant agents were applied in the precipitation experiments. Adsorption tests were performed in batch systems with constant stirring at 30 °C and at different pH values (7 and 9). Precipitation experiments were carried out in batch systems and the best conditions for silica removal were found using an L9 orthogonal array of the Taguchi method employing molar ratio, pH of wastewater, stirring time and temperature as experimental factors. Adsorption results showed that Ferrolox (Iron (III) hydroxide-base adsorbent) was the most efficient sorbent for reactive silica removal from synthetic solutions and the anodizing wastewater. Also, the reactive silica adsorption was higher at pH 9 as compared to that measured at pH 7 and the adsorbed quantity at pH 9 was 16.22 and 11.25 mg/g for the synthetic solution and anodizing wastewater, respectively. According to molecular simulation, the main interaction between Ferrolox and silica species was related to the formation of hydroxo-complexes and to the interaction of Fe with oxygen of silica species. Additionally, magnesium chloride was the best precipitating reagent for reactive silica achieving up to 87% removal. According to ANOVA analysis of Taguchi method, pH was the most influential factor during the precipitation of reactive silica with a variance value of 81.42, while values lower than 3 were obtained for the rest of parameters. Overall, the present work is reporting for the first time the removal of reactive silica from anodizing wastewaters with promising results that can be implemented at full scale for water reclamation, which may significantly contribute to manage water reservoir in the region sustainably. Graphical abstract: Image 1 Highlights: High silica removal from anodizing wastewater was obtained by precipitation method. MgCl2 .6H2 O was the most efficient precipitant agent for reactive silica removal. Iron ( III ) hydroxide based-sorbent was efficient in the adsorption of reactive silica.